Protein stability [determination] problems - Ahmad, Faizan (Frontiers in Molecular Biosciences, 2022)
Human health depends on the correct folding of proteins, for misfolding and aggregation lead to diseases. An unfolded (denatured) protein can refold to its original folded state. How does this occur is known as protein folding problem. One of several related questions to this problem is that how much more stable is the folded state as compared to the unfolded state. There are several measures of protein stability. In this article, protein stability is given a thermodynamic definition and is measured by Gibbs free energy change (ΔGD0) associated with the equilibrium, native (N) conformation ↔ denatured (D) conformation under physiological condition usually taken as dilute buffer (or water) at 25 °C. We show that this thermodynamic quantity (ΔGD0, where subscript D represents transition between N and D states, and superscript 0 (zero) represents the fact that the transition occurs in the absence of denaturant) can be neither measured nor predicted under physiological conditions. However, ΔGD can be measured in the presence of strong chemical denaturants such as guanidinium chloride and urea which are shown to destroy all noncovalent interactions responsible for maintaining the folded structure. A problem with this measurement is that the estimate of ΔGD0 comes from the analysis of the plot of ΔGD versus denaturant concentration, which requires a long extrapolation of values of ΔGD, and all the three methods of extrapolation give three different values of ΔGD0 for a protein. Thus, our confidence in the authentic value of ΔGD0 is eroded. Another problem with this in vitro measurement of ΔGD0 is that it is done on the pure protein sample in dilute buffer which is a very large extrapolation of the in vivo conditions, for the crowding effect on protein stability is ignored.